PDTM-09. Yap1 FUNCTION IN SEX-BIASED MEDULLOBLASTOMA FORMATION AND ANTI-TUMOR IMMUNITY. (11th November 2019) - Abdelfattah, Nourhan; Natarajan, Sivaraman; Chen, Yaohui; Chow, Kin-Hoe; Chen, Shu-hsia; Olson, James; Baskin, David; Yun, Kyuson
Abstract: Immunotherapies offer remarkable potential to provide robust therapeutic benefit. Patients suffering from medulloblastoma (MB), the most frequent pediatric brain malignancy, can especially benefit from this approach, minimizing the devastating side effects of aggressive radiation and chemotherapies that disrupt normal brain development. However, regulators of the immune landscape remain poorly understood and no effective immunotherapies exist yet for MB. Here, we describe a sex-dependent Yap1 function in fSmoM2;GFAPcre SHH-MB (SG) mouse model. We show that Yap1 is both a cell-autonomous regulator of MB stem-cells and a non-cell-autonomous regulator of immune infiltrates in SHH-MB. Yap1 deletion in SG mice results in increased neuronal differentiation, significantly extended survival, and enhanced infiltration of peripheral blood immune cells (including cytotoxic T-cells, neutrophils, and macrophages). Additionally, this rescue phenotype is observed in a sex-biased manner: 65% of Yap1f/f;fSmoM2;GFAPcre males are rescued in contrast to 35% of females. These observations implicate Yap1 as a mediator of sex-biased brain-tumor formation, either through direct modulation of MB cells and/or through indirectly mediating the MB immune landscape. We are currently testing the role of sex-specific differences in the developing mouse brain to elucidate context-dependent function of Yap1 in MB genesis and maintenance.